Coastal and marine ecosystem services valuation for policy and management - Tiziana Luisetti; R. Kerry Turner; David Hadley; Sian Morse-Jones (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2010)
Understanding the economic value of nature and the services it provides to humanity has become increasingly important. In this paper we review the progress to date on both the necessary conceptual framework and empirical valuation studies required to bolster decision support systems targeted at integrated coastal zone management goals. We first review definitions of ecosystem services. We then highlight and discuss the importance of: spatial explicitness; marginal changes; double-counting; non-linearities; and threshold effects. Finally, using UK case studies on managed coastal realignment, we highlight the usefulness of an ecosystem services sequential decision support system to environmental valuation and policy assessment.
Keywords: 330; Ecosystem services; Ecosystem valuation; Managed realignment; Choice experiment; Cost-benefit analysis; Umweltökonomik; Umweltgüter; Umweltschutz; Kosten-Nutzen-Analyse; Küstenschutz; Großbritannien